Microbial Effects from Biogas Slurry Application on Growing Phase of Turi (Sesbania grandiflora) - Nurzainah Ginting; Hasnudi; Yunilas; M.Adanan Purba (Jurnal Peternakan Integratif, 2019)
This research was conducted in Samosir Island, North Sumatera Province, Indonesiawhich has Inceptisol soil. As this type of soil is generally unfertile, since hundreds years ago,local people added ruminant faeces before planting. This research objective was to prove thatapplication of biogas slurry on growing phase of Turi (Sesbania grandiflora) plant improvedmicrobial population on soil thus plant quality. This research was conducted from May untilSeptember 2018. Research design was Completely Randomized Design (CRD) withtreatments slurry dosages which were P0: without slurry, P1: 10/ha/year and P2: 20/ha/year.Parameters were chemical composition of slurry, microbial type and population, plant height,total leaf, stem diameter, number of branch and leaf size. The results showed that P0 had nosignificant effect on every parameters while P1 and P2 improved microbial type andpopulation, plant height, total leaf, stem diameter, number of branch and leaf size (P <0.05).There was an increasing of microbial population in line with the increasing of slurry dosage.P2 contained the highest population of bacteria or fungal (F <0.05) compared to P0 or P1.